Maternal C-reactive protein and cytokine levels during pregnancy and the risk of selected neuropsychiatric disorders in offspring: A systematic review and meta-analysis. (October 2018) - Zhang, Jian; Luo, Wanjun; Huang, Pengcheng; Peng, Linrui; Huang, Qitao
Abstract: The pathophysiology of neuropsychiatric disorders is unclear. Increasing evidence has suggested maternal immune system dysregulation may be implicated in offspring's early brain development and related to an increased risk of neuropsychiatric disorders in offspring. The primary objective of this meta-analysis was to investigate the association of maternal CRP and cytokine levels with offspring's neuropsychiatric disorders. We identified relevant studies following a search of PubMed, Web of Science, EMbase database between January 1971 and February 2018. A meta-analysis was performed on studies which reported the association of prenatal maternal peripheral blood concentrations of CRP and cytokines with offspring's neuropsychiatric disorders. Results were reported according to PRISMA statement. Fifteen studies (six for maternal CRP, nine for maternal cytokines) were included in the meta-analysis, of which 80% were of high methodological quality. Random-effect meta-analysis showed that increasing maternal CRP (OR = 1.31, 95% CI 1.11–1.55, SMD = 0.15, 95% CI 0.06–0.24, P < 0.01), pro-inflammatory cytokine interleukin (IL)-8 (OR = 1.64, 95% CI 1.06–2.55, SMD = 0.27, 95% CI 0.03–0.52, P = 0.03) and anti-inflammatory cytokine IL-10 (OR = 2.16, 95% CI 1.30–3.59, SMD = 0.43, 95% CI 0.14–0.71, P < 0.01) were significantly associated with schizophrenia in offspring. The finding of our meta-analysis has identified significantly altered maternal CRP and cytokine concentrations in schizophrenia, strengthening evidence of maternal immune system dysregulation in neuropsychiatric disorders where inflammatory signals dominate.